2009
DOI: 10.1063/1.3187904
|View full text |Cite
|
Sign up to set email alerts
|

Antenna effects and improved efficiency in multiple heterojunction photovoltaic cells based on pentacene, zinc phthalocyanine, and C60

Abstract: Articles you may be interested inImproved photovoltaic performance of bilayer heterojunction photovoltaic cells by triplet materials and tetrapodshaped colloidal nanocrystals doping Appl. Phys. Lett. 95, 043101 (2009); 10.1063/1.3186074Effect of metal cathode reflectance on the exciton-dissociation efficiency in heterojunction organic solar cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…Singlet fission is particularly attractive because of the high quantum efficiency (B200%, triplet excitons per photon) in a few well-known organic semiconductors, such as pentacene and Tc, and the prospect of designing and synthesizing new singlet fission molecules 3,4 . Although several research groups have demonstrated solar cells and photodetectors using singlet fission materials [5][6][7][8][9][10] , we are far from understanding how to efficiently harvest singlet fission for enhanced solar energy conversion. Design principles for molecules with high singlet fission yields are starting to emerge 3,4 but little is known about how to optimally extract the two electron-hole pairs resulting from singlet fission.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Singlet fission is particularly attractive because of the high quantum efficiency (B200%, triplet excitons per photon) in a few well-known organic semiconductors, such as pentacene and Tc, and the prospect of designing and synthesizing new singlet fission molecules 3,4 . Although several research groups have demonstrated solar cells and photodetectors using singlet fission materials [5][6][7][8][9][10] , we are far from understanding how to efficiently harvest singlet fission for enhanced solar energy conversion. Design principles for molecules with high singlet fission yields are starting to emerge 3,4 but little is known about how to optimally extract the two electron-hole pairs resulting from singlet fission.…”
mentioning
confidence: 99%
“…One strategy of harvesting singlet fission for solar energy conversion is to form an interface between a singlet fission material (for example, Tc or pentacene) and an electron acceptor (for example, fullerene or inorganic semiconductor quantum dots) for multiple CT (refs [5][6][7][8][9][10]. A limitation of this approach is that CT processes from both the singlet and the triplet pair are possible 11 ; the former does not contribute to any increase in power conversion efficiency beyond the ShockleyQueisser limit and is difficult to avoid for most electron acceptors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, several groups have reported layered organic PVs composed of two donor layers [13][14][15][16][17][18][19]. Although different mechanisms, such as double exciton dissociation at the heterojunction of a centered ambipolar donor layer with both the acceptor layer and the other donor layer, have been proposed [13,14,18], an interlayer ET sensitization mechanism has been accepted [15,16,19] [20].…”
Section: Introductionmentioning
confidence: 99%
“…Although different mechanisms, such as double exciton dissociation at the heterojunction of a centered ambipolar donor layer with both the acceptor layer and the other donor layer, have been proposed [13,14,18], an interlayer ET sensitization mechanism has been accepted [15,16,19] [20]. However, in the three-layered donor stack, a donor layer placed farthest from the acceptor layer, corresponding to the donor layer on the left in Fig.…”
Section: Introductionmentioning
confidence: 99%